CCIE and CCDE Evolving Technologies Study Guide, First Edition - Edgeworth, Brad; Gooley, Jason; Rios, Ramiro Garza (Pearson IT Certification, 2018)
Prepare for the evolving technology components of Cisco's revised CCIE and CCDE written exams The changes Cisco made to its expert-level CCIE and CCDE certifications allow candidates to link their core technology expertise with knowledge of evolving technologies that organizations are rapidly adopting, including cloud services, IoT networking, and network programmability. This guide will help you efficiently master and integrate the knowledge of evolving technology that you'll need to succeed on the revised CCIE and CCDE written examinations. Designed to help you efficiently focus your study, achieve mastery, and build confidence, CCIE and CCDE Evolving Technologies Study Guide focuses on conceptual insight, not mere memorization. Focused specifically on the exams' evolving technologies components, it combines with track-specific Cisco Press certification guides to offer comprehensive and authoritative preparation for advanced Cisco certification. Understand the Internet of Things (IoT) from the perspective of business transformations, connectivity, and security Review leading IoT architectural models and applications Structure edge, fog, and centralized compute to maximize processing efficiency Recognize behavioral and operational differences between IoT networks and enterprise networks Gain a holistic understanding of public, private, or hybrid cloud environments that use VMs or containers Explore cloud service models, connectivity, security, scalability, and high availability designs. Master modern API-based programmability and automation methods for interacting with diverse network applications and devices Connect with the Cisco DevNet developer community and other key resources for Cisco network programming.